PENINGKATAN PRESTASI BELAJAR SISWA DALAM PEMBELAJARAN KIMIA DENGAN PENERAPAN COOPERATIVE LEARNING MODEL JIGSAW PADA KELAS X IPA3 DI SMA NEGERI 1 PADANG - Aswirna, Prima (Institut Agama Islam Negeri Imam Bonjol Padang, 2012)
The problem of this Classroom Action Research is how Cooperative Learning Model Jigsaw should be implemented in the learning of Chemistry at Grade X, Scince 3 of Senior High School 1 Padang.Â This study was done through the following stages such as Planning, Action, Observation, and Evaluation or Reflection.Â The results show among other that some important aspects were improved.Â The average score of each cycles show improvement in studentsâ mastery and total average of the three actions become 98 percent.Â It can be concluded that Cooperative Learning through Jigsaw technique improved studentsâ achievement of the subject being investigated.